Silver Nanoplates: Synthesis, Functional Applications and Translation Potential, A Systematic Literature Review - Yosia Nico Wijaya; Nurharis Munandar (Universitas Islam Raden Rahmat, Malang, 2026)
Silver nanoplates and related triangular nanoprisms provide edge- and tip-enhanced plasmonics that are attractive for sensing, catalysis, energy conversion, and biomedical concepts, yet translation is frequently limited by oxidative reshaping, ligand loss, and inconsistent reporting. This systematic literature review synthesizes peer-reviewed journal evidence published between 2015 and 2025 to clarify synthesis levers, structure-property-performance relationships, and application readiness. ScienceDirect and Google Scholar were searched (last update: 15 December 2025) and screened using a PRISMA 2020 workflow and PICOC framing. From 137 records, 23 studies met inclusion criteria for qualitative synthesis. Across the literature, reproducible performance most strongly tracks coupled control of lateral size and thickness via pH, chelators, and capping ligands, which tunes LSPR position and linewidth. Applications are most mature in plasmonic sensing, including rapid pathogen and small-molecule detection, while flow-compatible catalysis and device-integrated energy studies provide clearer pathways toward deployment. Key gaps remain in standardized morphology descriptors, long-term stability protocols, batch reproducibility, and leaching or toxicity evidence. Actionable guidance is provided for scalable synthesis, robust validation, and translation-focused reporting. Unlike earlier reviews that emphasize either plasmonic principles or single application niches, this review integrates synthesis control with stability and reporting standards to accelerate translation.